Influence of Brand Image, Price and Product Quality on Honda Product Purchasing Decisions Vario motorbike in Tangerang City - Prayoga, Riky Gilang (Majalah Ilmiah Bijak, 2024)
This research aims to analyze the influence of information, prices and purchasing decisions. The method used is multiple linear regression with the dependent variable being Purchase Decision and the independent variables being Brand Image, Price and Product Quality. The results of this research show that price and purchasing decisions have a significant effect on purchasing decisions